Integrated Experimental, Statistical, and Finite Element Analysis of Nanoparticle-Reinforced Polymer Composites for Advanced Structural Applications Completed with Bibliometric Analysis - Layla M. Nassir; Abdul-Rasool Kareem Jweri; Ehsan Sabah Al-Ameen; Ahmed Ali Farhan Ogai-li; Emad Kadum Njim; Firas Thair Al-Maliky; Alaa Abdulhady Jaber; Luttfi A. Al-Haddad; Mustafa I. Al-Karkhi (Bumi Publikasi Nusantara, 2026)
This study investigates the mechanical and tribological behavior of polyvinylidene fluoride (PVDF)/unsaturated polyester resin (UPR) composites reinforced with 1–5% multi-walled carbon nanotubes (MWCNTs). Research on PVDF-based nanocomposites has increased significantly, according to a quick bibliometric screening of Scopus-indexed publications. MWCNTs were found to be one of the most influential reinforcement keywords, indicating a high level of interest in mechanically optimized polymer systems worldwide. In this study, specimens were tested for tensile, flexural, hardness, impact, wear, and reversed-bending fatigue performance. Results reveal that 3% MWCNT provides optimal strengthening, improving tensile and flexural properties, hardness, wear resistance, and fatigue life while reducing void content. Finite element simulations using ANSYS aligned with experimental findings, showing deviations below 10%. Statistical analysis (ANOVA) confirmed significant effects of MWCNT content. Overall, PVDF/UPR–MWCNT composites demonstrate excellent potential for advanced lightweight structural applications.